Exploration of resistance/resilience against gastrointestinal nematode infection in Garole sheep - Ghosh, J D; Jas, Ruma; Bordoloi, Gautam (The Indian Journal of Animal Sciences, 2012)
Possible existence of resistance and/ resilience against gastrointestinal nematode (GIN) infection in 160 Garole sheep was explored under field condition. Monthly qualitative and quantitative faecal examinations and coprocultural examination of all the Garole sheep were performed for 1 year. Based on the monthly faecal egg count (EPG), after 1 year the sheep were divided into group (Gr) 1 showing consistently lowest EPG, Gr 2 with consistently moderate EPG and Gr 3 with consistently highest EPG. Thereafter blood sample was collected from representative number (6) of sheep in each group on 4 occasions at 1-month-interval for estimation of haemoglobin concentration (Hb) and packed cell volume (PCV). The overall prevalence of GIN in the sheep under study was 75.41%. Strongyle nematodes constituted 72.92% to which the highest contribution was of Haemonchus contortus (70.17%) followed by Oesophagostomum (15.08%), Trichostrongylus (9.75%), Strongyloides (2.75%) and hookworms (2.17%). The overall intensity of infection in terms of mean EPG was 422.37 with the highest in September (950.26) and the lowest (231.02) in March. The mean overall EPG of Gr1 (128.00) was significantly (P>0.05) lower than Gr 2 (434.38) and Gr 3 (704.73). The Hb and PCV values did not differ significantly due to the difference in intensity of infection (EPG) in the 3 groups of sheep.